CALCULATION OF CURRENT PARAMETERS OF POWER SYSTEM MODE WITH INCOMPLETE INITIAL DATA USING NEURAL MODELLING - Lezhnjuk, Petro; Rubanenko, Olena (Scientific Works of Vinnytsia National Technical University, 2015)
A mathematical model is offered which allows to find load power in a node at telemetry devices failure, using hybrid neural network and Sugeno algorithm of fuzzy conclusion.